Standard Tone Stability as a Manipulation of Precision in the Oddball Paradigm: Modulation of Prediction Error Responses to Fixed-Probability Deviants - SanMiguel, Iria; Costa-Faidella, Jordi; Lugo, Zulay R.; Vilella, Elisabet; Escera, Carles (Frontiers in Human Neuroscience, 2021)
Electrophysiological sensory deviance detection signals, such as the mismatch negativity (MMN), have been interpreted from the predictive coding framework as manifestations of prediction error (PE). From a frequentist perspective of the classic oddball paradigm, deviant stimuli are unexpected because of their low probability. However, the amount of PE elicited by a stimulus can be dissociated from its probability of occurrence: when the observer cannot make confident predictions, any event holds little surprise value, no matter how improbable. Here we tested the hypothesis that the magnitude of the neural response elicited to an improbable sound (D) would scale with the precision of the prediction derived from the repetition of another sound (S), by manipulating repetition stability. We recorded the EEG from 20 participants while passively listening to 4 types of isochronous pure tone sequences differing in the probability of the S tone (880Hz) while holding constant the probability of the D tone (1046Hz; p(D)=1/11): Oddball (p(S)=10/11); High confidence (7/11); Low confidence (4/11); and Random (1/11). Tones of 9 different frequencies were equiprobably presented as fillers (p(S)+p(D)+p(F)=1). Using a mass-univariate non-parametric, cluster-based correlation analysis controlling for multiple comparisons, we found that the amplitude of the deviant-elicited ERP became more negative with increasing S probability, in a time-electrode window consistent with the MMN (ca. 120-200ms; frontal), suggesting that the strength of a PE elicited to an improbable event indeed increases with the precision of the predictive model.